Robustness and relevance of predictive score in sudden cardiac death for patients with Brugada syndrome. (17th November 2020) - Probst, Vincent; Goronflot, Thomas; Anys, Soraya; Tixier, Romain; Briand, Jean; Berthome, Pauline; Geoffroy, Olivier; Clementy, Nicolas; Mansourati, Jacques; Jesel, Laurence; Dupuis, Jean-Marc; Bru, Paul; et al.
Abstract: Aims : Risk stratification of sudden cardiac arrest (SCA) in Brugada syndrome (Brs) remains the main challenge for physicians. Several scores have been suggested to improve risk stratification but never replicated. We aim to investigate the accuracy of the Brs risk scores. Methods and results : A total of 1613 patients [mean age 45 ± 15 years, 69% male, 323 (20%) symptomatic] were prospectively enrolled from 1993 to 2016 in a multicentric database. All data described in the risk score were double reviewed for the study. Among them, all patients were evaluated with Shanghai score and 461 (29%) with Sieira score. After a mean follow-up of 6.5 ± 4.7 years, an arrhythmic event occurred in 75 (5%) patients including 16 SCA, 11 symptomatic ventricular arrhythmia, and 48 appropriate therapies. Predictive capacity of the Shanghai score ( n  = 1613) and the Sieira ( n  = 461) score was, respectively, estimated by an area under the curve of 0.73 (0.67–0.79) and 0.71 (0.61–0.81). Considering Sieira score, the event rate at 10 years was significantly higher with a score of 5 (26.4%) than with a score of 0 (0.9%) or 1 (1.1%) ( P  < 0.01). No statistical difference was found in intermediate-risk patients (score 2–4). The Shanghai score does not allow to better stratify the risk of SCA. Conclusions : In the largest cohort of Brs patient ever described, risk scores do not allow stratifying the risk of arrhythmic event in intermediate-risk patient.